Moving Meals and Migrating Mothers: Culinary cultures, diasporic dishes and familial foodways - Tūm, ʿAbdallāh ʿUṯmān at-; Cassidy, Tanya (Demeter Press, 2021)
Cover -- Title Page -- Copyright -- Acknowledgments -- Contents -- Introduction -- PART I -- Chapter 1 -- Chapter 2 -- Chapter 3 -- PART II -- Chapter 4 -- Chapter 5 -- Chapter 6 -- PART III -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Notes on Contributors -- Cover Artist's Statement.